2008
DOI: 10.1016/j.dsr2.2008.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt, manganese, and iron near the Hawaiian Islands: A potential concentrating mechanism for cobalt within a cyclonic eddy and implications for the hybrid-type trace metals

Abstract: The vertical distributions of cobalt, iron, and manganese in the water column were studied during the E-Flux Program (E-Flux II and III), which focused on the biogeochemistry of cold-core cyclonic eddies that form in the lee of the Hawaiian Islands. During E-Flux II (January 2005) and E-Flux III (March 2005), 17 stations were sampled for cobalt (n =147), all of which demonstrated nutrient-like depletion in surface waters. During E-Flux III, two depth profiles collected from within a mesoscale coldcore eddy, Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
143
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(164 citation statements)
references
References 81 publications
(117 reference statements)
16
143
5
Order By: Relevance
“…Recent studies have found that micronutrient drawdown can be an important process in controlling the distribution of Co in ocean surface waters (Ellwood and van den Berg, 2001;Saito et al, 2004Saito et al, , 2005Ellwood et al, 2005;Noble et al, 2008). This contrasts with earlier reviews that characterized Co as controlled by scavenging removal processes (Whitfield and Turner, 1987;Nozaki, 1997).…”
Section: Introductioncontrasting
confidence: 46%
See 4 more Smart Citations
“…Recent studies have found that micronutrient drawdown can be an important process in controlling the distribution of Co in ocean surface waters (Ellwood and van den Berg, 2001;Saito et al, 2004Saito et al, , 2005Ellwood et al, 2005;Noble et al, 2008). This contrasts with earlier reviews that characterized Co as controlled by scavenging removal processes (Whitfield and Turner, 1987;Nozaki, 1997).…”
Section: Introductioncontrasting
confidence: 46%
“…This abundance of labile cobalt is likely important in providing a bioavailable form of Co to eukaryotic phytoplankton (Saito et al, , 2004. Moreover, the presence of measurable labile cobalt throughout the water column of the Ross Sea contrasts with observations in tropical and subtropical regions, where cobalt is often completely bound by strong ligands in the upper euphotic zone (Saito and Moffett, 2001;Saito et al, 2004Saito et al, , 2005Noble et al, 2008). Exceptions to this appear to be related to significant sources of cobalt, such as in the Peru Upwelling Region, where a large flux of cobalt is thought to enter the system as labile cobalt, and where large phytoplankton community shifts occurred concurrently with changes in cobalt speciation (Saito et al, 2004).…”
Section: Chemical Speciation Of Cobaltmentioning
confidence: 64%
See 3 more Smart Citations